DEVELOPMENT OF E-INFRASTRUCTURE IN THE SYSTEM OF EDUCATION AND SCIENCE OF UKRAINE - Зуб, Станіслав; Прокопенко, Андрій; Яловега, Ірина (New Collegium, 2020)
A transfer of grid technologies that were developed for the needs of the scientific community for use them in the educational environment is proposed. Specific areas of application and innovative prospects for the development of e-infrastructure in the educational environment of modern university are considered. To solve these tasks the article proposed to use the best practices of the Grid Enabled Remote instrumentation with Distributed Control and Computation project. The purpose of the project was to use the abilities of grid for the safe and remote joint work of the research teams for ensure monitoring and control of the instruments and transfer of experimental data that are generated and stored on the distributed scientific equipment in grid. The key element of the future research e-infrastructure become the instrument Element that consists of the connected set of services that provide all the necessary functionality for configuring, managing and monitoring the measuring devices like sensor, dummy and smart instruments or the complex scientific facilities. instrument Element ensures the interaction the devices with external grid. it is shown that grid provides all the technical capabilities for integrating educational and research environment of the modern universities. The use of grid technologies in distance learning form is aimed on students gaining practical skills in working with equipment of physical, chemical, biological and other educational and research laboratories. The aim of our research is to analyze the technical and socio-economic factors that influence the development of the research e-infrastructure of Ukraine. Using the principle of Responsible Research and innovation that distinguishes socially important innovations and research and approaches like design thinking we have proposed the own concept of building of national research e-infrastructure that must start from formation of educational e-infrastructure. Analysis shows that such consistency should become impetus for integration of the existing e-infrastructures of domestic science and education and will also contribute to the effective integration of future research e-infrastructure of Ukraine into European and world research e-infrastructures.